ANALISIS KARAKTERISTIK DEBITUR UMKM BIDANG PERTANIAN TERPADU BANK NTT KANTOR CABANG UTAMA KUPANG (CHARACTERISTICS ANALYSIS OF MICRO, SMALL AND MEDIUM ENTERPRISES (SMES) DEBTORS IN INTEGRATED AGRICULTURAL SECTOR AT NTT BANK -MAIN BRANCH OFFICE OF KUPANG - Solviana M. Makandolu; Johanis G. Sogen; Yusuf L. Henuk (Universitas Nusa Cendana, 2014)
The Micro, Small and Medium Enterprises (SMEs) in the economy have a very important role. A study with a survey method has been conducted to determine the factors that affect the rate of return on the Main Micro Credit (MMC) in agriculture at Bank NTT Main Branch Office of Kupang. The study aimed to describe the characteristics of the MMC debtors both smooth and non-current in the credit worthiness on Bank NTT Main Branch Office of Kupang. The sampling method used was nonproportionate cluster sampling. The number of samples selected were 80 debtors consists of 55 non-current debtors and 25 smoothly debtors. Results showed that the characteristics of MMC debtors of NTT Bank experiencing non performing loans mostly are no longer productive age, male sex, marital status, highest level of education was junior high school or equivalent, as well as having a large number of family. Business characteristics that affect the noncurrent collectibility is the amount of assets that is less than IDR 20 million, turnover of less than IDR 5 million, credit limit of more than IRD 30 million, operating revenues of less than IDR one million as well as the field of business done is not a primary business but only as a companion of primary business. ABSTRAK Usaha Mikro, Kecil dan Menengah (UKM) dalam perekonomian memiliki peran yang sangat penting. Sebuah studi menggunakan metode survei telah dilakukan untuk mengetahui faktor-faktor yang mempengaruhi tingkat pengembalian Kredit Mikro Utama (KMU) di bidang pertanian di Bank NTT Pusat Kupang. Penelitian ini bertujuan untuk mendeskripsikan karakteristik debitur KMU baik lancar dan tidak lancar dalam kelayakan kredit di Bank NTT Pusat Kupang. Metode sampel yang digunakan adalah cluster sampling nonproportionate. Jumlah sampel yang dipilih adalah 80 debitur terdiri dari 55 debitur tidak lancar dan 25 debitur lancar. Hasil penelitian menunjukkan bahwa karakteristik debitur KMU di Bank NTT Pusat Kupang mengalami kredit bermasalah yang sebagian besar tidak lagi usia produktif, jenis kelamin laki-laki, status perkawinan, tingkat pendidikan tertinggi adalah SMP atau sederajat, serta memiliki sejumlah besar keluarga. Karakteristik usaha yang mempengaruhi kolektibilitas lancar adalah jumlah aset yang kurang dari Rp 20 juta, omset kurang dari Rp 5 juta, batas kredit lebih dari Rp. 30 juta, pendapatan usaha kurang dari Rp satu juta serta usaha yang dilakukan bukan usaha utama tetapi hanya sebagai usaha sampingan.